ANTHROPOMETRIC INDICATORS OF CHILDREN LIVING IN AREAS WITH DIFFERENT LEVELS OF AIR POLLUTION - Sotlikova Zhonigul Rakhimovna; Obdalova Dilorom Makhmudovna (Modern American Journals, 2025)
Relevance of the study. Currently, in the context of a pronounced demographic decline, maintaining and improving the health of children is an important task for society and the state. Furthermore, studying indicators of physical development, the level of functioning of the body's main systems, and the body's adaptive capacity, reflecting its degree of resilience to environmental factors, is among the most important areas of hygiene research. It is known that the majority of the country's population, including children, live in cities, which are hubs of industry and transportation. In these cities, assessing the impact of man-made chemical factors on children's physical and mental development is crucial. However, most studies examine the impact of environmental factors on the morphofunctional and psychophysiological state of schoolchildren and adolescents. Insufficient attention has been paid to preschool-age children in the scientific literature. There are isolated studies in certain regions devoted to studying the incidence of diseases and the physical and neuropsychological development of preschoolers living in ecologically polluted areas.